Mental health diagnosis and perceptions of juvenile delinquent behaviors: the impact of ethnicity - Malach, Steffany L., author; Rosen, Lee A., advisor; Bloom, Larry J., committee member; Bundy-Fazioli, Kimberly, committee member; Swaim, Randall, committee member (Colorado State University. Libraries, 2010)
Recent reports indicate that as much as 60 to 75 percent of youth in the juvenile justice system have been diagnosed with a mental health disorder. Reports further indicate a wide disparity of disposition at all stages of juvenile judicial decision-making according to a juvenile’s ethnicity. Delinquent behavior is often a symptom of commonly occurring childhood mental health disorders, and differences based on ethnicity in both entrance into the juvenile justice system, outcomes of adjudication, and referral to mental health resources has yet to be widely explored. The present study sought to examine how the presence of a mental health diagnosis affects perceptions of juveniles of different ethnicities who engage in delinquent behaviors. Eight hundred forty six female and male university undergraduates read one of six vignettes depicting a juvenile, who was presented as Hispanic, African American, or Non-Hispanic White, engaged in a delinquent behavior. The juvenile was identified as having either ADHD, Conduct Disorder, Bipolar Disorder, Major Depression, Abuse/Neglect, or No Mental Illness. Participants expressed their perception of the juvenile’s culpability for the given behavior, their conceptualization of the juvenile’s character, and rated the amount of punishment and treatment they recommended. Results indicated that knowledge about a juvenile’s ethnicity did not affect the amount of psychiatric treatment or seventy of punishment recommended for the juvenile, nor did it significantly impact overall conceptualization or willingness to forgive the Juvenile. Having received information about the juvenile’s mental health status, however, was shown to affect how positively or negatively the juvenile was viewed in general, the amount of psychiatric treatment recommended, and the severity of recommended punishment. Results further indicated that female participants were more likely to forgive the juvenile for his behavior than were males. Implications of these findings for the juvenile justice system are discussed.
Covers not scanned.
Keywords: Juvenile delinquency -- United States -- Psychological aspects -- Cross-cultural studies; Juvenile delinquency -- United States -- Cross-cultural studies